Identification of Tax Allowance Policies and Mechanisms in Indonesia - Marlina, Reni; Bahri, Efri Syamsul; Wibowo, Hendro; Wiharjo, Suyadi Murdi (ITQAN: Journal of Islamic Economics, Management, and Finance, 2023)
The government issued a tax allowance policy to increase the amount of investment in Indonesia. This policy is given to Foreign Investors (PMA) and Domestic Investors (PMDN). This research aims to identify the policy and implementation mechanism of tax allowance in Indonesia. This research uses a qualitative method with a descriptive approach. First, the study found that the tax allowance policy is contained in article 31A, paragraph 21 of Law Number 7 of 1983 on Income Tax. Then, in Law Number 36 of 2008 on the Fourth Amendment to Law Number 7 of 1983 on Income Tax and Government Regulation Number 78 of 2019 on Income Tax Facilities for Capital Investment in Certain Fields of Business and/Or in Districts -Specific Areas. Furthermore, the tax allowance mechanism is regulated in the Regulation of the Minister of Finance of the Republic of Indonesia Number 11/PMK.010/2020 Regarding the Implementation of Government Regulation Number 78 of 2019 Regarding Income Tax Facilities for Capital Investment in Certain Fields of Business and/or in Certain Districts.